CONTEXTUAL TEACHING AND LEARNING SEBAGAI MODEL PEMBELAJARAN DASAR-DASAR EKONOMI - Nurseto, Tejo (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2006)
Abstract This research was intended to know the extent to which Contextual Teaching and Learning (CLT) are able to overcome practical problems in compliance with the students’ ability to construct a concept from what they learned. The research subjects are the students of the academic years 2003/2004 who take the Introduction to Economic Science. This research involved 40 first semester students, one lecturer as the researcher and the executor of the action, two observer lecturers. Since there is lack of time in the accordance with the grouping and the students’ classification takes time, two methods are used to improve: the students’ participation in discussing the results of their discussion, the students’ way in revealing describing oral description review, the students’ capability in construction concept. It is found that CTL has the following weaknesses: the frequent use of CTL method makes the students boring. For the students with high level of learning motivation it is ex citing because they have chance to express more opinions, but for those with low level of learning motivation it is not interesting. Keywords: Contextual Teaching and Learning